ANALISIS MODERASI KURS DAN CONSUMER CONFIDENCE INDEX PADA HUBUNGAN INFLASI DAN SUKU BUNGA TERHADAP IHSG - Nuuron A'la, Ahmad Zidni; Sucipto, Agus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.04.TAHUN.2025, 2025)
Global uncertainty, inflation and interest rates are major challenges to the performance of the Jakarta Composite Index (JCI) in Indonesia. The exchange rate and Consumer Confidence Index (CCI) are often considered as moderating factors that can strengthen or weaken the effect of inflation and interest rates on the JCI. This study examines the effect of inflation and interest rates on the JCI for the period 2014-2023 with exchange rate and CCI as moderating variables. Secondary data obtained from the Indonesia Stock Exchange (IDX) and other economic sources were analyzed using quantitative methods, including descriptive analysis, classical assumption test, and Moderated Regression Analysis (MRA). The study identified that inflation has no significant effect on the JCI, while interest rates have a negative impact. The exchange rate did not moderate the relationship between inflation and interest rates with the JCI, but the CCI proved to strengthen the relationship. The findings contribute significantly to the academic and practical understanding of the capital market in Indonesia. In addition, the study results can be a strategic reference for investors and policy makers to formulate more appropriate investment decisions to deal with stock market fluctuations due to inflation and interest rates.